Economic Pressures and Social Dynamics in Developing Life Skills of Only Children - Dinda Ayu Nurrahmania Aurora; Dito Aditia (Journal of Development Economic and Social Studies, 2026)
The development of life skills is a strategic aspect in determining the quality of only children in facing increasingly complex social, economic, and cultural challenges, as several previous studies have shown that economic and social factors significantly influence this development. The aim of this research is to analyze economic pressures and social dynamics influencing the development of life skills in only children, with the aim of formulating evidence-based strategies. This research applied a qualitative descriptive method with a phenomenological approach, where data were collected through in‑depth interviews with informants, and the findings were analyzed using SWOT to formulate strategies for developing the life skills of only children in the context of economic pressures and social dynamics. The development of life skills in only children is shaped by economic pressures and social dynamics that can both strengthen and weaken their growth. While strengths such as resilience, responsibility, and optimism, along with opportunities like social participation and entrepreneurial spirit, foster independence and social awareness, weaknesses and threats, ranging from emotional burdens to workplace injustice and limited job prospects, highlight their vulnerability. Therefore, effective strategies must leverage strengths and opportunities while addressing weaknesses and threats, through initiatives such as entrepreneurship training, community engagement, creative learning environments, proactive career planning, and livelihood programs, ensuring that only children are better equipped to achieve independence and stability in challenging socioeconomic contexts. The findings of this research provide guidance for only children in developing life skills, even when facing economic pressures and social dynamics.